Co-inheritance of variants/mutations in Malaysian patients with Crohn s disease - Chua, K.H.; Ng, C.C.; Hilmi, I.; Goh, K.L. (2012)
Crohnâs disease is a chronic, relapsing inflammatory bowel disease; it affects the mucosa and deeper layers of the digestive wall. Two Crohnâs disease patients who carried the JW1 variant and two patients who carried the SNP5 variant were investigated for other co-inherited polymorphisms that could influence Crohnâs disease development. Based on the sequencing results, a homozygous 5ê-UTR-59 G to A variant in exon 1 (SNP6) was observed in a patient who carried SNP5, while a heterozygous SNP6 variant was detected in the other patient who carried SNP5. No other associated mutations or polymorphisms were detected in the two patients who carried the JW1 variant of the CARD15/NOD2 gene.